Philosophical criminology - Millie, Andrew (Bristol : Policy Press, 2017)
'Philosophical Criminology' asks big questions about how we get along with one another and what happens when we do not. Structured around six core philosophical ideas concerning our relationships with others - values, morality, aesthetics, order, rules, and respect, this work builds upon Andrew Millie's past work with value judgments, aesthetics, and respect to consider the shifting boundaries of criminology.
Previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 30, 2017).
Keywords: Criminology -- Philosophy; True Crime; Social services & welfare, criminology